2008
DOI: 10.1093/jjco/hym161
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Selection Criteria for Active Surveillance in Japanese Patients with Stage T1cN0M0 Prostate Cancer

Abstract: The primary endpoint, '%PSADT > 2y', did not meet the pre-specified decision criteria. Further prospective study with revised program and endpoint is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
70
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 18 publications
0
70
0
Order By: Relevance
“…For seven men who discontinued AS, reasons are unknown. Kakehi et al 26 reported that during the observation period, no serious adverse events were observed: not in the AS program group and not in those men who chose immediate treatment.…”
Section: Active Surveillancementioning
confidence: 99%
See 3 more Smart Citations
“…For seven men who discontinued AS, reasons are unknown. Kakehi et al 26 reported that during the observation period, no serious adverse events were observed: not in the AS program group and not in those men who chose immediate treatment.…”
Section: Active Surveillancementioning
confidence: 99%
“…Klotz et al, 23 Carter et al 24,25 and Kakehi et al 26 have all initiated studies regarding the value of AS (Table 2). Klotz et al 23 reported on the long-term clinical results of a large, AS cohort with localized PC at the beginning of this year.…”
Section: Active Surveillancementioning
confidence: 99%
See 2 more Smart Citations
“…The first is the Japanese AS study that was carried out in favourable-risk PCa patients, starting in 2002. 13,14 The second is the PRIAS-JAPAN study (Japan has been participating in the PRIAS study as PRIAS-JAPAN since 2010). As of April 2012, 32 institutions had participated and approximately 250 patients were enrolled in the PRIAS-JAPAN study.…”
mentioning
confidence: 99%